DISTRIBUSI UKURAN DAN HUBUNGAN PANJANG BOBOT DAN FAKTOR KONDISI IKAN KAKAP MERAH (Lutjanus gabbus) YANG DIPERDAGANGKAN DI TPI RAJAWALI MAKASSAR - Nur Fitriyani S; Muhammad Jamal; Nadiarti Nurdin Kadir (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2025)
Snapper has great economic value and is one of the fishery export products. Apart from being an export product, snapper also has a relatively high market price and is very popular with the public for consumption, utilization increases. This causes snappers to face significant stress. This study aims to analyze the size distribution, length-weight relationship, and condition factors of Red Snapper (Lutjanus gibbus) traded at TPI Rajawali Makassar. Data collection uses the stratified random sampling method. Length and weight data were analyzed using the Sturges formula for size distribution, regression analysis for the long-weight relationship, and condition factor calculation. The results showed that the number of samples was 238 with lengths ranging from 12.2–33.5 cm. The highest size distribution was in the length class of 19.0–21.8 cm as many as 64 heads, while the lowest was at 31.9–34.3 cm as many as 5 heads. The length-weight relationship of fish was allometric negative (b = 2.78), which showed faster increase in length than weight. The condition factor of the fish ranged from 0.62-9.16 with an average of 1.03, which indicated that the physiological condition of the fish was in the good category.